Depression and Anxiety as Risk Factors for Morbidity and Mortality after Organ Transplantation: A Systematic Review and Meta-Analysis() - Dew, Mary Amanda (Transplantation, 2015)
BACKGROUND: Depression and anxiety are common mental health problems in transplant populations. There is mixed evidence concerning whether they increase morbidity and mortality risks post-transplant. If such associations exist, additional risk reduction strategies may be needed. METHODS: Four bibliographic databases were searched from 1981 through September, 2014 for studies prospectively examining whether depression or anxiety (determined with diagnostic evaluations or standardized symptom scales) affected risk for post-transplant mortality, graft loss, acute graft rejection, chronic rejection, cancer, infection, and rehospitalization. RESULTS: Twenty-seven studies (10 heart, total n=1,738; 6 liver, n=1,063; 5 kidney, n=49,515; 4 lung, n=584; 1 pancreas, n=80; 1 mixed recipient sample, n=205) were identified. In each, depression and/or anxiety were typically measured pre- or early post-transplant. Follow-up for outcomes was a median of 5.8 years (range:0.50–18.0). Depression increased the relative risk (RR) of mortality by 65% (RR=1.65, 95% CI:1.34,2.05; 20 studies). Meta-regression indicated that risk was stronger in studies that did (v. did not) control for potential confounders(p=.032). Risk was unaffected by type of transplant or other study characteristics. Depression increased death-censored graft loss risk (RR=1.65, CI:1.21,2.26, 3 studies). Depression was not associated with other morbidities (each morbidity assessed in 1–4 studies). Anxiety did not significantly increase mortality risk (RR=1.39, CI:0.85,2.27, 6 studies) or morbidity risks (assessed in single studies). CONCLUSIONS: Depression increases risk for post-transplant mortality. Few studies considered morbidities; the depression-graft loss association suggests that linkages with morbidities deserve greater attention. Depression screening and treatment may be warranted, although whether these activities would reduce post-transplant mortality requires study.